Peran Pemerintah Desa dalam Meningkatkan Kualitas Pelayanan Administrasi di Kantor Desa Tenilo Kecamatan Tilamuta - Indrawati Indrawati; Karmila Damariani Radjak; Irfan Gani (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The role of the village government in improving the quality of administrative services at the village office is part of an effort to realize professional public services that focus on community satisfaction. The village government acts both as a policymaker and a service provider, responsible for delivering an orderly, fast, and transparent administrative system. This research was conducted at the Tenilo Village Office in Tilamuta District. This study aims to determine the extent of the village government's role in improving the quality of administrative services at the Tenilo Village Office, Tilamuta District, Boalemo Regency. This study uses a qualitative research approach. Data collection techniques include observation, interviews, and documentation. The data sources consist of both primary and secondary data. The data analysis technique used is descriptive qualitative analysis, which includes data reduction, data presentation, and conclusion drawing. The research findings at the Tenilo Village Office in Tilamuta District indicate that the government has played an active role in enhancing the quality of administrative services. However, there are still several inhibiting factors in improving service quality. Internal factors include: (1) inadequate service facilities, (2) limited skills and capabilities, and (3) budget constraints. Meanwhile, external challenges involve: (1) lack of community participation.